KEPASTIAN HUKUM BAGI PENCIPTA LAGU TERKAIT LARANGAN MEMBAWAKAN LAGU OLEH PIHAK TERTENTU. - Simamora, Hara Dongan; Yuhelson, Yuhelson; Halim, Anriz Nazaruddin (SENTRI: Jurnal Riset Ilmiah, 2024)
Moral rights, in Copyright Law are regulated by several articles, starting from article 5 to article 7. Moral rights of creators are prohibited from being removed, changed or damaged. Parties who use a work are prohibited from removing, changing or damaging. Regarding moral rights, it does not regulate the creator’s right to prohibit other parties from using their work. In Das Sollen Copyright Law does not regulate the creator’s right to prohibit certain parties, but in Das Sein it is often found that creators prohibit other parties from performing songs they have created. The problem is how to implement the rules regarding the right of prohibition by songwriters to certain parties and what is the legal certainty about prohibiting songs from being performed by the creator to certain parties. Analyze the theory of legal certainty and the theory of authority. Normative juridical research using interviews with National Institute of Collective Management. Law, Conceptual, Analytical and Case Approaches. The book source contains Copyright Law. Legal sources contain primary legal materials and secondary legal materials. Identify positive legal rules and sources relevant to the legal issues being studied. Analysis of legal materials is carried out by carrying out grammatical and systematic interpretation. The legal construction used is a legal refinement construction. Conclusion everyone is allowed to use a work for commercial purposes with the obligation to pay royalties through National Institute of Collective Management. The inconsistency of article 9 paragraph (2) with article 23 paragraph (5) on the one hand gives the creator power but on the other hand this power is reduced so that the use of songs in a performance does not require permission from the creator as long as they have paid royalties to National Institute of Collective Management. Suggestions require deeper knowledge regarding the author’s authority in accordance with the Copyright Law. Directorate Gemeral of Intellectual Property must immediately revise the regulations regarding inconsistencies in article 9 paragraph (2) and article 23 paragraph (5), which is expected to be a solution that can addres musicians problems in a relatively quick time.